Physical activity as protective factor against COVID-19 disease - Ametta, A.; Francavilla, V. C.; Polito, R.; Monda, M.; Messina, A.; Monda, V.; Sessa, F.; Daniele, A.; Messina, G. (Journal of Human Sport & Exercise, 2020)
The Coronavirus Pandemic has forced millions of people around the world to look at home. This resulted, as a consequence, in a remodelling of the lifestyle; in this scenario the correct nutrition combined with regular physical activity becomes fundamental for health. Although the sedentary lifestyle of a few weeks involves risks such as lowering the immune system, it favours overweight and obesity, high blood pressure, metabolic disorders, depression and anxiety, and in some subjects they react to the risk of onset of cardiovascular disease, diabetes and other diseases. The importance of healthy lifestyle is crucial to prevent also viral infection. Indeed, as reported by many data literature, during lung infections, IL-6 and TNF-a create the pathway between adipose tissue and lung system demonstrating the important involvement of adipose tissue in lung diseases. In obese condition, adipose tissue endocrine function is altered. There is an imbalance in the production of pro-inflammatory cytokines such as IL-6 and TNF-a and anti-inflammatory mediators such as IL-10. In the light of these evidences, the immune response is influenced by nutritional status and by physical activity which are able to reduce pro-inflammatory mediators and increase anti-inflammatory mediators such as IL-10 . In addition, the power of viral infection is influenced by host predisposition. For these reasons, a correct lifestyle, and physical activity are a valid strategy in the prevention and treatment of not metabolic diseases also of inflammatory diseases.